Getting the Most out of Social Media: What Is Social Media? - Jessica C. Fernandez; Joy N. Rumble (EDIS, 2015)
Agriculturalists can use social media as a powerful tool for marketing their products and establishing a brand identity. This 3-page EDIS publication, which focuses on defining social media for agriculturalist and identifying the multiple platforms agriculturalist can use, is the first in the Getting the Most out of Social Media series. The goal of this series is to help agriculturalists understand how social media can work for them. The series also discusses the various social media platforms and how to use social media strategically and wisely. Written by Jessica C. Fernandez and Joy N. Rumble, and published by the UF Department of Agricultural Education and Communication, August 2015. (Photo credit: tanuha2001/iStock/Thinkstock.com)